Cognitive Behavioral Therapy for Antenatal Depression in a Pilot Randomized Controlled Trial and Effects on Neurobiological, Behavioral and Cognitive Outcomes in Offspring 3–7 Years Postpartum: A Perspective Article on Study Findings, Limitations and Future Aims - Bleker, Laura S.; Milgrom, Jeannette; Sexton-Oates, Alexandra; Parker, Donna; Roseboom, Tessa J.; Gemmill, Alan W.; Holt, Christopher J.; Saffery, Richard; Connelly, Alan; Burger, Huibert; de Rooij, Susanne R. (Frontiers in Psychiatry, 2020)
Purpose of review: We describe the evidence on associations between prenatal depression and child neurodevelopmental outcomes and we critically evaluate the results of one of the first randomized controlled trials on the effects of antenatal Cognitive Behavioural Therapy for depression and anxiety on child buccal cell DNA-methylation, brain morphology, behaviour and cognition approximately 5 years postpartum.